Indoor air quality and thermal comfort in elderly care centers - Mendes, A (2015)
This study explored environmental variables and buildings characteristics in 22 elderly care centers (ECCs) in Portugal. Indoor environmental parameters were measured twice for a total of 141 sampling sites. Each site was assessed for PM10, PM2.5, total volatile organic compounds (TVOC), formaldehyde, CO, CO2, total bacteria and fungi. Thermal comfort (TC) parameters were measured according to ISO 7730:2005 and a building characterization was performed. The overall PM2.5 mean concentration of the 22 ECC was above international reference levels in summer and winter seasons. TVOC, bacteria, CO and CO2 showed significantly higher indoor levels compared to outdoor, in both seasons. Indoor PM10, TVOC, bacteria and CO2 present significant differences between seasons. TVOC, bacteria and CO2 show significant variation between ECC rooms and 4% of fungi samples were positive for pathogenic Aspergillus species. The winter predicted mean vote (PMV) index showed a ‘slightly cool’ thermal sensation scale which may potentiate respiratory tract infections. The predicted percent of dissatisfied people (PPD) and PMV indices show significant differences by season. The building variables ‘Insulation’, ‘Heating Ventilation’ and ‘Windows frames’ were significantly associated to chemical, biological and TC parameters. ‘Bacteria’, ‘Fungi’, ‘Temperature’, Relative Humidity’, and ‘PPD index’ are the mostly affected by building characteristics. Insulating ceilings, walls, and windows could improve winter season TC, providing health benefits to ECC residents.